Patrimônio documental da faculdade de serviço social da UFPA: gestão para preservação da memória - SILVA, Ivonete Conceição Marques da (2017)
This study aims to raise awareness about the importance of documentary management for the preservation of the documentary heritage of the Social Service College of the Federal University of Pará (UFPA). The methodology used was based on bibliographical research and documentary analysis to justify the concepts related to the theme. The empirical field of research was aimed at the secretariat of the Social Service College of UFPA. Data collection was done through participant observation through the direct contact of the researcher with the reality of the research actors (secretaries and manager of the Social Service College of UFPA). In addition to interview, with questions asked openly and that were answered by the actors of the research in an informal conversation. The results showed that the preservation of documentary heritage contributes to the strengthening of the history and memory of the Institutions and guarantees the right of every citizen to access information. It was concluded that the absence of documentary management in the Social Service College secretariat compromises the main purpose of archival documents, which is to serve for administrative efficiency, as well as the preservation of the historical/cultural documents essential for the memory of the University.